Drama in Fostering Students’ Speaking Skills: A Systematic Review on Benefits and Problems - Fitri Rahmawati Astiandani; Ali Mustofa (English Department, Faculty of Humanities, Andalas University, 2021)
Drama is pedagogy with a fairly complete component that involves the body, mind, emotions, and senses in order to build individual relationships with true-life situations so that being active in language learning is needed by students. This paper will closely explore the benefits and problems of implementing drama during the process of teaching and learning a language. In language teaching, drama has been proposed as an effective way to encourage the students’ speaking skills. Essentially, drama provides more benefits, not only in students’ speaking skills but also in other aspects. However, some problems may arise in the process of drama-based language teaching. By cross-checking and reviewing eclectically from different sources, this paper presents a critical analysis of several empirical works on drama techniques used in the context of language learning. To generalize the notion, drama is indeed precious in language learning. Nevertheless, several problems in its implementation need to be considered to achieve learning objectives properly. The review results showed that some problems that may appear during the implementation of drama were undisciplined in time management, chaotic atmosphere, the usage of the first language (L1), and status at school. Hence, several suggestions are provided as solutions to the drama problems confronted by teachers.